Concurrent training in the conditional planning of elite rugby player - Camillini, A.; D'Amen. G.; Izzo, R. (Science, Movement & Health, 2018)
The alternation of resistance and endurance training, known as Concurrent Training (CT), has been gaining increasing interest in the scientific community for some years now. Different studies have suggested combining endurance with resistance training because if the training of these two capacities is designed appropriately, the functional and performance level rises positively. Sports like rugby it is essential to train these two conditional skills, since the rugby player is required to run for short distances and repeatedly. The match lasts a lot and run for 80 minutes on a field, opposing rivals requires appropriate training, not all aerobic capacity, but also very high levels of strength and power. Despite the countless studies done to best combine the training of these two capacities without creating interference, we still do not have clear guidelines to avoid it altogether. This work is a practical proposal of how the CT can be employed through an intra-session and inter-session training in an elite rugby team.